Animal health at the crossroads : preventing, detecting, and diagnosing animal diseases (National Academies Press, 2005)
The confirmed case of "mad cow" disease (BSE) in June 2005 illustrates the economic impact of disease outbreaks, as additional countries closed their markets to U.S. beef and beef products. Emerging diseases also threaten public health--11 out of 12 of the major global disease outbreaks over the last decade were from zoonotic agents (that spread from animals to humans). Animal Health at the Crossroads: Preventing, Detecting, and Diagnosing Animal Diseases finds that, in general, the U.S. animal health framework has been slow to take advantage of state-of-the-art technologies being used now to protect public health; better diagnostic tests for identifying all animal diseases should be made a priority. The report also recommends that the nation establish a high-level, authoritative, and accountable coordinating mechanism to engage and enhance partnerships among local, state, and federal agencies, and the private sector.